2019
DOI: 10.46568/pjass.v10i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation in Primary Level English and Urdu Textbooks in Pakistan

Abstract: The representation of gender in school textbooks is an area that has been researched in different contexts for decades. It is an area worth investigation because it has been established through research that gender biased textbooks provide hurdles for gender equality in many ways. Taking this as a point of departure this paper aims to examine the representation of male and female in primary level English and Urdu textbooks in Pakistan. To achieve its aim three public and private publishers i.e. AFAQ, National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…This is also in line with most of the other studies which found how Pakistani textbooks taught on various levels support the patriarchal structure and reinforce the existing inequalities (See, e.g. Ali & Hussain, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…This is also in line with most of the other studies which found how Pakistani textbooks taught on various levels support the patriarchal structure and reinforce the existing inequalities (See, e.g. Ali & Hussain, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…2. Ali, R., & Hussain, L. (2019). Gender representation in primary level English and Urdu textbooks in Pakistan.…”
Section: Methodsmentioning
confidence: 99%
“…The textbook regime in Pakistan is comprised of curriculum bureaus and the textbook boards constituted by each provincial ministry of education in its domain. The most recent studies (R. Ali & Hussain 2019;Iqbal, Saleem, & Ahmad 2019;Sultan, Shah, & Fazal 2019;Waqar & Ghani 2019) highlighted how the textbook regimes in Pakistan perceived women in Pakistani society and ascribed to them stereotypical roles in different stories found in textbooks. These findings were not different from the earlier studies that analysed textbooks (Aziz 1993;Mirza 2006;Nayyar & Salim 2005) in spite of more women taking up the role of textbook writers and editors but still the leading roles were given to male writers and editors.…”
Section: Islamization and Education In Pakistanmentioning
confidence: 99%
See 2 more Smart Citations